Investing in the Ummatic Cause: The Philanthropic Activities of ‘Abd Allah ibn ‘Alawi al-’Attas (d. 1929) - Alwi Alatas; Syed Mohammad Chaedar Syed Abdurrahman Al Yahya (IAIN KUDUS, 2024)
Indexed by Scopus